Prognostic impact of PTK6 expression in triple negative breast cancer - Yuexia Chen; Wei Qu; Jianhong Tu; Liu Yang; Xingxing Gui (BMC, 2023)
Abstract Background The aim of this study was to investigate the expression of PTK6 in different groups of triple negative breast cancer and its impact on prognosis. Methods Retrospective study of a total of 209 surgical specimens of breast cancer were identified by IHC or FISH methods as triple negative,and divided into a lymph node metastasis positive (LNM +)group (n = 102) and a lymph node metastasis negative(LNM-) group (n = 107) according to the lymph node status of the surgical specimen. PTK6 expression was detected by IHC technique in all surgical specimens. PTK6 expression and clinicopathological features was explored by Chi-square test. The prognosis of different groups of patients was analyzed by Kaplan-Meier survival analysis and COX analysis. Results The incidence of PTK6 expression in the LNM + group (78.4%) was significantly higher than in the LNM- group (28%). Clinicopathological analysis showed that PTK6 expression in the LNM + group was negatively correlated with the 5-year survival of patients. Kaplan-Meier analysis showed that only PTK6 expression in the LNM + group was negatively correlated with OS and DFS. COX analysis also showed that PTK6 expression and N stage were independent prognostic factors for DFS in the LNM + group. No correlation was observed between HER2 and PTK6 expression in any of the groups. Conclusions This study suggests that PTK6 promotes tumor development and was associated with poor prognosis in the LNM + group of triple negative breast cancer. Inhibition of PTK6 may be a new approach for the treatment of triple negative breast cancer patients, especially those with metastasis.